Modal identification and stiffness degradation of concrete block masonry buildings - Avila, Leonardo (2013)
A new construction system for masonry buildings is analysed. Identification of modal parameters has been carried out in two structural solutions by using this system namely reinforced and unreinforced symmetric two-story concrete block masonry buildings. Experimental shaking table tests were developed on these buildings by incremental inputs. Traditional modal analysis by using low amplitude input motion was made before and after dynamic tests and stiffness degradation has been correlated. Mode shapes, mode frequencies, damping ratios and damage identification through the test are discussed.